Scleral lens prescription and management practices: Emerging consensus. Issue 1 (February 2023) - Schornack, Muriel M.; Fogt, Jennifer; Nau, Amy; Nau, Cherie B.; Harthan, Jennifer S.; Cao, Dingcai; Shorter, Ellen
Highlights: This study confirmed corneal irregularity as the most common indication for scleral lens wear. The fitting process for scleral lenses is comparable to that of other specialty lenses. The mean diameter of scleral lenses is approximately 16 mm. A majority of patients in this sample wore lenses with spherical landing zones. Care regimen commonly featured daily cleaner, hydrogen peroxide disinfection, and single-use vials of nonpreserved saline. Abstract: Purpose: To describe international scleral lens prescription and management practices across multiple practice types. Methods: For this cross-sectional study, scleral lens practitioners were asked to complete an electronic survey that requested information about a single scleral lens patient. Data collected included practitioner demographics (practice type, country, years of experience) and patient indications for scleral lens wear, fitting process, lens design, and care products. Results: Data were collected for 259 patients (419 eyes). Most participants (60%) practiced in the US, 75% worked primarily in community practice, and 58% claimed more than 5 years' experience fitting scleral lenses. Indications for scleral lens wear were corneal irregularity (87%), ocular surface disease (9%), and uncomplicated refractive error (4%). During the fitting process, the mean (SD) number of lenses ordered was 2.4 (1.6) (range, 1–16 lenses) during 3.8 (2.4) visits (range, 1–18 visits). Of patients, 62% used a daily surfactant cleaner, 47% used hydrogen peroxide disinfection, and 67% used single-use vials of nonpreserved saline. Mean lens diameter was 16.2 (1.1) mm (range, 11.8–23.0 mm). The landing zones were spherical (64%), toric (26%), quadrant-specific (7%), and custom (3%) designs. Optical power was spherical in 70%, toric in 27%, and higher-order aberration correcting in 3% of lenses. Only 5 lenses had multifocal optics. Conclusions: General consensus regarding prescribing patterns (lens design, wearing schedules, care products) between US vs non-US, community vs academic, and new vs established providers is reported in this study. Relatively low percentages of patients wearing lenses with advanced landing zones or optical designs suggest that these new options have not been widely adopted.